On the first nu(6) anti-aligned librating asteroid family of Tina - Carruba, V. [UNESP]; Morbidelli, A. (Wiley-Blackwell, 2011)
Asteroid families are groups of bodies identified in the space of proper elements or of frequencies that share a common origin in the collisional break-up of their progenitors. Their dynamical evolution is shaped by the interaction with the local web of mean-motion and secular resonances, and by non-gravitational effects, such as the 'Yarkovsky' and 'Yarkovsky-O'Keefe-Radzievskii-Paddack' (YORP) effects. Thus, obtaining information on their age and original ejection velocity field is generally a difficult task. Recently, two families were found to have a large fraction of members in the non-linear secular resonance z(1): the Agnia and Padua families. Conserved quantities of the z(1)resonance allowed for a more precise determination of their ages and ejection velocity fields. So far, however, no family was known to be in a linear secular resonance, such as the nu(6) resonance, although individual asteroids were known to be in nu(6) anti-aligned librating states. The nu(6) resonance occurs when there is a commensurability between the frequency of precession of the pericentre of an asteroid and that of Saturn. As a consequence, in librating states, the resonant argument oscillates around a stable point. In anti-aligned librating states, the resonant argument oscillates around the stable point at 180 degrees. Here we show that the newly identified Tina family is characterized by having all its members in such a state, making it the only family in the asteroid belt known to be completely embedded in a secular resonance configuration. This rare dynamical configuration limits the maximum eccentricity of Tina members, preventing them from experiencing Martian close encounters and forming a stable island of a new dynamical type. The current dispersion of asteroid resonant elements suggests that the family should be at least 2.5 Myr old, while Monte Carlo simulations including the Yarkovsky and YORP effects suggest that the Tina family should be 170+20(-30) Myr old.
Keywords: celestial mechanics; minor planets, asteroids: general